2010
DOI: 10.2478/s11536-009-0117-3
|View full text |Cite
|
Sign up to set email alerts
|

In-vivo effects of nociceptin and its structural analogue [Orn9] nociceptin on the antioxidant status of rat blood and liver after carrageenan-induced paw inflammation

Abstract: AbstractThe production of reactive oxygen species (ROS) in cells is well balanced with their elimination by the antioxidant defence system. This balance is essential for maintenance of physiological conditions, and its disturbance (oxidative stress) has been suggested as a potential pathogenic mechanism in a variety of diseases, accompanied by inflammation. In this study, the in-vivo effects of nociceptin (N/OFQ(1–13)NH2) and its structure analogue [Orn9]N/OFQ(1–13)NH2 were stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Previous researches revealed that carrageenan injection caused excessive production of free radical. The involvement of oxidative stress in the acute inflammatory process had been already described by several authors [ 1 , 38 40 ]. The tested oils', once in contact with the skin, lipophilic compounds (tocopherols, sterols, and polyunsaturated fatty acids) seeped into the stratum corneum by percutaneous intercellular absorption and then joined the epidermis and the dermis [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 89%
“…Previous researches revealed that carrageenan injection caused excessive production of free radical. The involvement of oxidative stress in the acute inflammatory process had been already described by several authors [ 1 , 38 40 ]. The tested oils', once in contact with the skin, lipophilic compounds (tocopherols, sterols, and polyunsaturated fatty acids) seeped into the stratum corneum by percutaneous intercellular absorption and then joined the epidermis and the dermis [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 89%
“…In fact, inflammation induces excessive production of reactive oxygen species (ROS) involved in the genesis of oxidative stress, which generates oxidative imbalance [ 46 ]. Against oxidative stress condition, defense systems produce antioxidant enzymes, such as SOD, CAT, and GPx [ 47 ]. In the present work, we found that the carrageenan injection generates a highly significant decrease in the activities of SOD, CAT, and GPx in the untreated group at the tissue compared with the control group ( p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have shown that CG decreases the total glutathione (GSH/GSSG) level and superoxide dismutase activity (Cu,Zn‐SOD) and increases the glutathione peroxidase (GPx) and glucose‐6‐phospate dehydrogenase (Glu‐6‐P‐DH) activities, as measured in post‐nuclear homogenate of the inflamed paw . It increases the LPO but does not change the blood haemoglobin content, haematocrit value, GSH/GSSG level and antioxidant enzyme activities in the erythrocytes; CG‐induced imbalance in liver is manifested by increased LPO and decreased GSH/GSSG level …”
Section: Introductionmentioning
confidence: 99%
“…19 It increases the LPO but does not change the blood haemoglobin content, haematocrit value, GSH/GSSG level and antioxidant enzyme activities in the erythrocytes; CG-induced imbalance in liver is manifested by increased LPO and decreased GSH/ GSSG level. 20 According to Oyanagui,13 superoxide anion radical (O 2 -) participates in the prostaglandin-phase swelling (2-4 h) of , together with peroxynitrite and hydroxyl radical ( • OH) formed with its participation, are of significance for the acute inflammation and inflammatory pain. 12,15,21 Carrageenan inflammatory model also takes place in studying the effects of different antidepressant drugs.…”
Section: Introductionmentioning
confidence: 99%